Working with Hannah : a special girl in a mainstream school - Wise, Liz, 1955- (RoutledgeFalmer, 2000)
This book is a unique and detailed snapshot of the first years of schooling for a child with Down's Syndrome. Written by her classroom assistants, the book shows how inclusion can be a success not only for the child and family but also for the.